Exploring the mechanisms and mode of action of bioactive compounds from marine Streptomyces albidoflavus against breast carcinoma cells - Abir M. Shata; Mokhtar Saeed Rejili; Manal M. El-Naggar; Samy A. El-Asser; Ahmed A. Saleh; Elsayed E. Hafez; Faouzi Haouala; Amany S. Youssef (BMC Biotechnology)
Abstract Breast cancer remains one of the most lethal diseases for women worldwide. Marine populations are considered a vast reservoir for novel bioactive metabolites, particularly marine Actinomycetes, which are known to produce various bioactive compounds with antitumour, antibacterial, and antifungal properties. A promising new marine strain was isolated and identified as Streptomyces albidoflavus strain EgyAB2 (16 S rRNA gene sequence accession number ON680945.1). The anticancer activity of the extracted compounds was tested in the MCF7 cell line using a sulforhodamine B (SRB) bioassay, which revealed an IC50 of 0.36 µg/ml compared to the chemotherapeutic drug 5-fluorouracil (0.35 µg/ml). Additionally, the anticancer activity was confirmed by a dimethyl-thiazol-diphenyl-tetrazolium bromide (MTT) bioassay, which showed an IC50 of 17.46 µg/ml. The mode of action of the treated breast carcinoma (apoptotic effect) was studied via qRT-PCR, revealing a significant role in anticancer treatment. Although the extracted compounds exhibited high antioxidant activity in the diphenyl-2-picrylhydrazyl (DPPH) radical-scavenging assay, they presented an IC50 of 8.92 µg/ml and an inhibition percentage of 56.08%. Chemical characterisation was performed via GC‒MS, 1 H-NMR, and FTIR spectroscopy analyses, revealing the presence of 2-D N-methyl imidazole, 2-nonadecene, 1-D-2-methyl imidazole, and propane dinitrile, all of which exhibit antitumour activity.